Recurrent Olfactory Neuroblastoma Treated With Cetuximab and Sunitinib: A Case Report. Issue 18 (May 2016) - Wang, Lizhi; Ding, Yan; Wei, Lai; Zhao, Dewei; Wang, Ruoyu; Zhang, Yuewei; Gu, Xuesong; Wang, Zhiqiang
Abstract : Abstract: Olfactory neuroblastoma (ONB) is a rare cancer originating in the olfactory epithelium of the nasal vault. The recurrence rate of ONB is high, as the standard treatment of surgery followed by radiotherapy and/or chemotherapy is usually unsuccessful. The use of targeted therapy based on individual genomic variations after cancer relapse has not been reported. Here, we present the case of a 44-year-old man who was diagnosed with recurrent ONB and treated with a regimen developed using whole exome sequencing. Potential targets were first identified and then matched to appropriate drugs. Gene mutations in the genes encoding EGFR, FGFR2, KDR, and RET were discovered in the patient's tumor tissue by whole exome sequencing and the patient was treated with a combination of the targeted drugs cetuximab and sunitinib. Five days after treatment, enhancement magnetic resonance imaging showed a 65% reduction in tumor size, and the Visual analog scale headache scores went down to 2/10 from 10/10. Repeat imaging at 1 month showed a complete response. This study represents the first demonstration of an effective personalized treatment of ONB by targeted drugs, and sheds light on how precision medicine can be used to treat recurrent ONB that fails to respond to routine tumor resection, radiotherapy, and/or chemotherapy.